2015
DOI: 10.1186/s12913-015-1056-0
|View full text |Cite
|
Sign up to set email alerts
|

Combining administrative data feedback, reflection and action planning to engage primary care professionals in quality improvement: qualitative assessment of short term program outcomes

Abstract: BackgroundImproving primary care for chronic disease management requires a coherent, integrated approach to quality improvement. Evidence in the continuing professional development (CPD) field suggests the importance of using strategies such as feedback delivery, reflective practice and action planning to facilitate recognition of gaps and service improvement needs. Our study explored the outcomes of a CPD intervention, named the COMPAS Project, which consists of a three-hour workshop composed of three main ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Improving prescribing behavior requires a coherent, integrated approach 33. Many educational and support strategies have been investigated to close evidence practice gaps and their results have highlighted the difficulty in achieving substantial impacts with such programs 11, 12, 13, 33, 34, 35.…”
Section: Discussionmentioning
confidence: 99%
“…Improving prescribing behavior requires a coherent, integrated approach 33. Many educational and support strategies have been investigated to close evidence practice gaps and their results have highlighted the difficulty in achieving substantial impacts with such programs 11, 12, 13, 33, 34, 35.…”
Section: Discussionmentioning
confidence: 99%
“…The program's main goals were to engage primary care providers in continuous QI, improve interprofessional collaboration, and enhance the quality of care for priority chronic diseases [32]. The innovation central to COMPAS was the way in which it combined the use of population-based data to provide feedback on chronic disease performance, engaged participants in a process of critical reflection around their performance, and facilitated the development of QI action plans through a process of collaborative problem solving [32,33]. These components were delivered as part of a half-day continuing professional development workshop for primary care teams from a same territory.…”
Section: Development and Previous Evaluation Of The Compas+ Programmentioning
confidence: 99%
“…These components were delivered as part of a half-day continuing professional development workshop for primary care teams from a same territory. COM-PAS integrated notions of the Chronic Care Model [34] and Model for Improvement [35] and was guided by a well-articulated program theory of change [32,33]. An evaluation of 10 workshops on diabetes management [33] revealed that COMPAS was effective in engaging participants and helping them recognize gaps between current practice and those outlined in clinical guidelines.…”
Section: Development and Previous Evaluation Of The Compas+ Programmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality improvement science offers methods and frameworks to support the adoption of evidence based practice (Meyers, Durlak & Wandersman, 2012) and audit feedback, critical reflection and action planning are considered useful strategies in the planning stage of practice change (Vachon et al, 2015). Despite the value placed on partnership working between researchers and practitioners to facilitate improved evidence based practice (Pentland et al, 2011), the perspectives of clinicians working with individuals with ASD are rarely reported (Rogers, Goddard, Hill, Henry & Crane, 2015).…”
Section: Introductionmentioning
confidence: 99%